Ultra-wide void denuded zone near composite grain boundary in micro-nano crystalline 304L steels. (15th July 2023) - Gao, Zhiying; Huang, Jia; Liu, Haocheng; Ge, Wei; Luo, Fengping; Zhang, Bowen; Liu, Guoying; Sun, Baoru; Shen, Tongde; Xue, Jianming; Wang, Yugang; Wang, Chenxu
Abstract: Grain boundaries in materials alter the behaviors of point defects and can subsequently affect their properties and performance. Here we report the formation of the ultra-wide void denuded zone (VDZ) with a width of up to about 650 nm, near the composite grain boundary (CGB) in Micro-Nano composite 304 L stainless steels (MN304-Las). Three kinds of MN304-Las with different nanocrystalline grain sizes but the same microcrystalline grain sizes were irradiated by 6 MeV Au 3+ ions to a peak dose of 216 dpa at 600 ℃. The strong ability to absorb and accommodate vacancies of CGB plays an important role in the formation of ultra-wide VDZ. Graphical abstract: Image, graphical abstract